Генный подход к созданию сложных информационных управляющих систем - Левыкин, В. М.; Евланов, М. В.; Скляров, А. Я. (My University, 2001)
Розглядається новий підхід до організації проектування складних інформаційних управляючих систем (ІУС). Висунута ідея генного підходу, викладені основні концепції та напрямки реалізації генного підходу до створення і експлуатації складних ІУС. Розглянуто основні види робіт, що вимагають реалізації в рамках генного підходу при створенні ІУС. Запропоновано структурну схему ІУС, розроблена з урахуванням вимог генного підходу. Відзначено основні напрямки досліджень в області реалізації технології генного проектування, які здатні надати конкретні практичні результати. A new approach to the design of complex information control systems (IСS) is considered. The idea of the gene approach has been advanced, basic concepts and directions of the implementation of the gene approach to the creation and operation of complex IСS have been outlined. The main types of work that require implementation within the framework of the gene approach for the creation of IСS are considered. A structural diagram of the IСS, developed taking into account the requirements of the gene approach, is proposed. The main directions of research in the field of the implementation of the technology of genetic design, which are able to provide concrete practical results.
Keywords: информационная управляющая система; эволюционное проектирование; информационный ген; параллельное проектирование